Global crop introduction drives host jumps, turning native pathogens into emerging diseases - Uma Crouch; Andrew Paul; Ignazio Carbone; Uwe Braun; Bailey Pelt; Gerald Holmes; Susumu Takamatsu; Dan-Ni Jin; Shu-Yan Liu; Michael Bradshaw (Proceedings of the National Academy of Sciences, 2026)
Global crop movement has traditionally been viewed as a major driver of emerging plant diseases through the introduction of pathogens into naïve environments. Here we show that the reverse process, introducing crops into regions containing endemic pathogens already adapted to related native hosts, is an equally powerful but underrecognized mechanism of disease emergence. Using multilocus phylogeny, haplotype networks, SplitsTree analysis, and molecular clock dating of both fresh and century-old herbarium specimens, we reconstructed the global history of powdery mildews infecting strawberries and raspberries. We reveal that these fungi comprise ancient, geographically structured, host-specialized lineages rather than a single cosmopolitan species as previously assumed. North American lineages infecting strawberries ( Podosphaera shepherdiae ) and Eurasian lineages infecting strawberries ( P. fragariae ) trace their origins to native hosts, predating modern agriculture by millions of years. Raspberry-infecting lineages showed similar patterns of local endemism and host association. These findings demonstrate that emerging plant diseases can arise not only when pathogens move globally, but also when nonnative crops are introduced into landscapes containing long-established native pathogens. This work highlights the importance of taxonomic resolution and herbarium genomics for identifying the true origins of agricultural diseases and for understanding the evolutionary pathways that give rise to modern epidemics.